1995
DOI: 10.1155/1995/462964
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Pattern in the Relapses of Crohn's Disease and Ulcerative Colitis in British Columbia

Abstract: Ulcerative colitis (UC) reportedly has a seasonal variation of exacerbations. No seasonal variation of relapses in Crohn's disease (CD) has been reported. A retrospective study of the monthly distribution in the relapses of inflammatory bowel disease (IBD) demonstrated seasonality in both UC and CD. From 1971-93, 226 patients (CD=139, UC=87) with regular follow-ups for at least 13 consecutive months were analyzed. In the study period, 592 relapses occurred in CD patients and 300 in UC patients. The peak relaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…When examining the studies that were not included in the meta-analysis, it seems that IBD exacerbation tended to occur slightly more frequently in warmer seasons. First, among the ten studies that reported a significant correlation between seasonal variation and IBD exacerbation, six reported a significant correlation with spring or summer [ 22 , 25 , 26 , 46 , 48 , 50 ], and the remaining three reported a correlation with winter or autumn [ 18 , 19 , 49 ]; in one study, both spring and autumn were reported ( Table 1 ) [ 20 ]. Second, two studies that reported the relationship between short-term extreme temperature change and IBD exacerbation support our hypothesis that warmer seasons were associated with more IBD exacerbations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…When examining the studies that were not included in the meta-analysis, it seems that IBD exacerbation tended to occur slightly more frequently in warmer seasons. First, among the ten studies that reported a significant correlation between seasonal variation and IBD exacerbation, six reported a significant correlation with spring or summer [ 22 , 25 , 26 , 46 , 48 , 50 ], and the remaining three reported a correlation with winter or autumn [ 18 , 19 , 49 ]; in one study, both spring and autumn were reported ( Table 1 ) [ 20 ]. Second, two studies that reported the relationship between short-term extreme temperature change and IBD exacerbation support our hypothesis that warmer seasons were associated with more IBD exacerbations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, only 6 out of 20 studies reported information on the duration of IBD morbidity, location of lesions, or medications administered [ 20 – 24 , 50 ]. Moreover, 7 out of 20 studies did not report the number of patients who experienced IBD exacerbations [ 18 , 20 , 26 , 27 , 49 , 51 , 52 ], and 6 of the 11 studies reported different numbers of patients and cases of exacerbations [ 19 , 21 , 22 , 25 , 48 , 50 ]. The abovementioned factors might have resulted in the underestimation or overestimation of the pooled estimate results of the meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations